EDUKASI DAN KESADARAN MASYARAKAT TENTANG PENYAKIT JAMUR KUKU PADA PENDULANG INTAN DI CEMPAKA KOTA MADYA BANJARBARU - Ratih Dewi Dwiyanti; Leka Lutpiatina; Aima Insana (UPPM Poltekkes Kemenkes Banjarmasin, 2026)
Diamond miners are one type of job that deals daily with wet and dirty places. Diamond miners work while wearing boots, but because the mining areas are filled with water, their feet are always damp and submerged in dirty water, which supports the growth of fungus. The objective of this activity is to enhance community health knowledge about fungal nail diseases and to reduce the incidence of fungal infections by providing antifungal medication to diamond miners in the area of the Tiung River in Cempaka, Banjarbaru. The methods used in this activity included pre-tests, presentation of materials, observation, post-tests, and the administration of antifungal medication. This activity involved 29 participants consisting of 5 females and 24 males. The results of the community service showed increased knowledge among partners regarding fungal infections of the nails based on the questionnaire results. As a result of the observation, it was found that all participants showed symptoms of fungal infection in their toe nails. Monitoring and evaluation were conducted 3 weeks after the counseling and observation activities, during which antifungal medication was distributed. It was concluded that the counseling activities could enhance the knowledge of the diamond miners